Enhanced degradation of furfural by heat-activated persulfate/nZVI-rGO oxidation system: Degradation pathway and improving the biodegradability of oil refinery wastewater. Issue 6 (December 2020) - Rahmani, Alireza; Salari, Mehdi; Tari, Kamran; Shabanloo, Amir; Shabanloo, Nader; Bajalan, Somaye
Graphical abstract: Highlights: The HAP/nZVI-rGO was optimized for the treatment of oil refinery wastewater. The synergy between HAP and PS/nZVI-rGO significantly reduced the activation energy. S O 4 - was the predominant radical in the oxidation system. The nZVI-rGO maintained its performance for five consecutive oxidation cycles. The HAP/nZVI-rGO can be developed for high-temperature wastewater. Abstract: Oil refinery wastewater is characterized by high values of temperature and furfural concentration. Furfural is a toxic and non-biodegradable substance in aqueous media that its absorption through the skin causes acute neurological and pulmonary effects. In this study, a heat-activated persulfate (HAP) system in combination with reduced graphene oxide-supported nano zero-valent iron catalyst (nZVI-rGO) was developed for oil refinery wastewater treatment. Five operational parameters regarding furfural removal were statistically modeled by an orthogonal central composite design (OCCD) and then optimized by genetic algorithm (GA) technique. The main characteristics of the nZVI-rGO as well as its reusability were investigated by field emission scanning electron microscopy (FESEM), energy-dispersive X-ray spectroscopy mapping (EDX-mapping), X-ray diffraction analysis (XRD) and vibrating sample magnetometer (VSM) analysis. The optimum values for the solution temperature, nZVI-rGO dosage, persulfate (PS) concentration, solution pH and reaction time were predicted to be 70 °C, 1.25 g L −1, 4.28 mmol L −1, 5.46 and 50 min, respectively. Under the optimized conditions, the experimental furfural removal efficiency in HAP/nZVI-rGO and HAP oxidation systems were obtained to be 97.80 and 68.20 %, respectively. Sulfate radical ( S O 4 - ) has greater participation in furfural mineralization than hydroxyl radical ( H O ). The major intermediates resulting from the furfural mineralization were short-chain acids including acetic acid and formic acid. Regardless, almost complete furfural mineralization was achieved after 100 min of the oxidation reaction. The optimized HAP/nZVI-rGO process was able to significantly improve the biodegradability of wastewater by more than 2 times.